2015
DOI: 10.1038/tpj.2015.18
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation, expression and ontogeny of sulfotransferase SULT2A1 in humans

Abstract: Sulfotransferases (SULTs) are enzymes involved in the metabolism of several endogenous molecules. The activity and expression exhibit inter- and intra-individual variations due to age and genetic variation. The aims of this study were to compare the gene expression of SULT2A1 in fetal and adult livers, to study the intra-individual tissue distribution, and investigate if expression is associated with a SULT2A1 copy number variation polymorphism. In contrast to other drug metabolizing enzyme systems the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Since most of the accessible research in this area was undertaken in a rodent model, which does not translate directly to humans, our data on PXR and SULT2A1 expressions in humans are novel and may have a future translational clinical repercussion. More research is needed to understand the enigmatic role of SULT2A1 in the development of liver disease [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since most of the accessible research in this area was undertaken in a rodent model, which does not translate directly to humans, our data on PXR and SULT2A1 expressions in humans are novel and may have a future translational clinical repercussion. More research is needed to understand the enigmatic role of SULT2A1 in the development of liver disease [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…region of the SULT2A1 gene) and that rs296361 has no causal effect on the SULT2A1 phenotype. It is important to note that a copy number variation (CNV) in the SULT2A1 gene locus has also been described (Ekström and Rane, 2015) and has been associated with the urinary excretion of DHEA-sulfate and testosterone-sulfate (Schulze et al, 2013). However, the frequency of the CNV appears to be much lower than that of rs296361.…”
Section: Sulfonation Of 25-hydroxyvitamin Dmentioning
confidence: 99%
“…Finally, it is population genetics influencing steroid sulfation pathways and the interindividual variability in drug response. Several coding SNPs in SULT genes influence an individual's sulfation capacity (Louwers et al 2013), but also gene number variations have been reported for SULT2A1 (Ekstrom & Rane 2015) and other sulfotransferases (Marto et al 2017). In fact, the SULT2A1 gene seems to be more evolvable than, for example, PAPS synthases (Mueller et al 2015); Ensembl (https:// www.ensembl.org) lists various expansions of this gene in different lineages with an eight-genes-comprising gene cluster in mice (Zerbino et al 2018), while a set of two PAPS synthase genes is highly conserved in vertebrates (van den Boom et al 2012).…”
Section: Substrate Specificity and Regulation Of Sulfotransferasesmentioning
confidence: 99%